LOGOS IN JOHN 1: 1-18 As an Analysis of The Implications of Logos for Christian Religious Education - Sendow, Mieke Nova; Tarumingi, Denny Adri; Tewu, Peggy Sandra; Ratag, Linda Patricia (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2025)
Logos is a term known to many Christians. The word logos is expressed by humans, translated from Greek meaning: word, saying, message or word. The word Word also refers to what dwells in the human mind such as; mind, reason or logic. The problem is that many people discuss and write about logos theologically but no one has written about logos who have become human beings and are present in the midst of Jewish society to educate and teach. This research aims to explore the meaning of logos that have become human in Jesus Christ based on the Gospel of John 1:1-18 and raise its implications for Christian Religious Education. The research method used to answer this problem is a qualitative research method with literature study work that supports a historical criticism approach to the text. From this discussion, the author offers the result as a new perspective that the church needs to implement the meaning of the logos, through Christian education for the congregation.